Cerium Dioxide Thin Films Using Spin Coating. (26th September 2012) - Channei, D.; Nakaruk, A.; Phanichphant, S.; Koshy, P.; Sorrell, C. C.
Abstract : Cerium dioxide (CeO 2 ) thin films with varying Ce concentrations (0.1 to 0.9 M, metal basis) were deposited on soda-lime-silica glass substrates using spin coating. It was found that all films exhibited the cubic fluorite structure after annealing at 500°C for 5 h. The laser Raman microspectroscopy and GAXRD analyses revealed that increasing concentrations of Ce resulted in an increase in the degree of crystallinity. FIB and FESEM images confirmed the laser Raman and GAXRD analyses results owing to the predicted increase in film thickness with increasing Ce concentration. However, porosity and shrinkage (drying) cracking of the films also increased significantly with increasing Ce concentrations. UV-VIS spectrophotometry data showed that the transmission of the films decreased with increasing Ce concentrations due to the increasing crack formation. Furthermore, a red shift was observed with increasing Ce concentrations, which resulted in a decrease in the optical indirect band gap.